Income Tax Incentives to Increase Zakat Receipt - Meri Teja Arum (GoResearch - Research & Publishing House, 2025)
This study is a literature study with descriptive qualitative research type with literature review that seeks to describe examine the structural and implementation challenges in integrating zakat and income tax within a fiscal incentive framework in Indonesia. Although zakat is legally recognized as a deductible from taxable income, its application remains suboptimal. This is evidenced by Indonesia’s low tax ratio and zakat revenues that capture only a small fraction of their potential. The literature reveals that while income tax incentives could theoretically increase zakat collection, they may also reduce overall tax revenue if not properly designed and implemented. The findings emphasize the urgent need for fiscal reform that promotes systemic integration, digital reporting mechanisms, fiscal literacy, and institutional synergy to achieve both social justice and economic welfare.